Addressing the health needs of people with disabilities in India - Suraj Singh Senjam; Amarjeet Singh (Wolters Kluwer Medknow Publications, 2020)
In India, the number of people with disabilities is continuously growing over the past few decades. The figure is expected to increase due to population aging, with a resultant increase in chronic health conditions. The health of people with disabilities is a relatively neglected and ignored area. Further, the disabled face poor access to healthcare and frequently encounter discrimination or stigmatization. These situations make them more vulnerable to many comorbidities in their health, making severe compromises in their quality of life. Therefore, people with disabilities need special healthcare than people without disabilities. There is a need for sensitization of all health-care providers to ensure quality, affordable, and accessible health-care services for people with disabilities. To address the health-care needs of people with disabilities to the maximum, Ministry of Health, Government of India should incorporate appropriate guidelines in various national health programs and work together with a relevant ministry.